Academic evaluation : review genres in university settings - Hyland, Ken, 1951-; Diani, Giuliana (Palgrave Macmillan, 2009)
Summary from OCLC: Academic criticism can be highly fraught and threatening, potentially wounding to the reviewed author and disruptive to the discipline, but it occurs routinely in review genres. This book explores how academics publically evaluate each others' work. Focusing on blurbs, book reviews, review articles, and literature reviews, the international contributors to the volume show how writers manage to critically engage with others' ideas, argue their own viewpoints, and establish academic credibility while simultaneously navigating these risky interactions.
Keywords: vysoké školy; evaluace; vysokoškolské kvalifikační práce; odborné texty; odborné písemné práce; vědecké práce; publikační činnost; vědecké publikace; recenze; literární kritika; universities and colleges; evaluation; academic theses; professional texts; professional papers; scientific reports; publication activity; scientific publications; reviews; literary criticism; kolektivní monografie; collective monographs